(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: It is necessary to ensure the surgical safety in order to ensure the patient safety in health facilities. This study aims to provide the current situation and the influenced factors to the adherence of surgical safety procedure amongst health providers in Phuc Yen Regional Hospital in 2022. Method: The study used cross-sectional design by using surgical safety checklist for 180 surgeries. Data collection period is May-June 2022 at Phuc Yen Regional Hospital. Findings: The study pointed out a number of problems in adhering surgical safety checklist. About 16.1% had errors in pateint identification during sign-in phase. The 2 criteria implant checks and equipment and device check had low compliance rates, 45% and 63.9%, respectively, during before start of surgical anesthesia phase. Estimation of complications had 56.1% compliance rate during before open of surgical incision phase. And a quarter of surgeries did not count and confirm that instruments, swabs, and sharps are complete. Conclusion: There had many issues in adhering surgical safety checklist. We recommend strengthening monitoring and evaluation and increase training and fostering on applying surgical checklist for health providers, buy new medical equipment and ensure the maintainance and repair.